The effectivity of hypnobreastfeeding on the success of exclusive breastfeeding by mothers giving birth at Dian Dwi Anggraini Independent Midwifery Practice in Bogor Regency - Rochmawati Rochmawati; Gracea Petricka; Arini Kusmintarti (Alma Ata University Press, 2023)
Background:Stunting is an indicator of chronic malnutrition due to a long period of insufficient food intake. The prevalence rate of stunting in Indonesia reached 24.4% in 2021. Generally, problems related to linear growth in toddlers are frequently disregarded because it is still considered as normal as long as the child’s weight has met the standard. Several studies stated that stunting is associated with an increased risk of morbidity and mortality, as well as inhibited development of motoric and mental abilities. To decrease the prevalence of stunting, specific intervention in the form of exclusive breastfeeding needs to be carried out. The coverage of exclusive breastfeeding in Indonesia was 52.5%. Feeding the baby exclusively with breast milk up to the age of 6 months has been recommended by the World Health Organization (WHO). However, various obstacles occurred in the breastfeeding process cause the mothers unable to provide the babies with exclusive breast milk. One of the inhibiting factors of breast milk production is the psychological factor, which is the occurrence of stressors in breastfeeding mothers. One of the efforts which can be done to relieve stress in breastfeeding mothers is by applying hypnobreastfeeding. It is a natural effort carried out by providing positive affirmations for the breastfeeding process when mothers are in a very relaxed or very concentrated state. Objectives : This study aims to figure out the effect of hypnobreastfeeding on the success of giving exclusive breastfeeding.Methods: This research employed quantitative descriptive analysis with a quasi-experimental and control group post-test-only design.Results : The results of this study obtained the effectiveness of hypnobreastfeeding on the success of exclusive breastfeeding. It is indicated by statistical values with a p-value of < 0.05., and the effect is 5.5 times greater than that of the group without hynobreastfeeding. Conclusions : Referring to the high effectiveness of hypnobreastfeeding on the success of exclusive breastfeeding shown in this study, the researchers confirmed that hypnobreastfeeding is an action that must be given by health workers when accompanying mothers in labor.